(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The agent paradigm is currently attracting much research. A mobile agent is a particular type of agent with the ability to migrate from one host to another, where it can resume its execution. In this paper we consider security issues that need to be addressed before multi-agent systems in general, and mobile agents in particular, can be a viable solution for a broad range of commercial applications using the concept of bioinformatics. This is done by considering the implications of the characteristics given to agents and the general properties of open multi-agent systems. The paper then looks in some more detail at security technology and methods applicable to mobile agent systems.